The development of health protection and social care services in Poland and in the countries of the European Union - Agata Szczukocka (Economic and Environmental Studies (E&ES), 2018)
Health is considered to be the greatest invaluable good. This article concentrates on the level of advancement of medical services in Poland and in certain countries of the European Union. This research uses such indicators as: expenditure on health care, the level of morbidity, mortality, sick leaves, number of doctors, hospitals, as well as the average life expectancy. Dynamic indices were used in the determination of developmental trends. To capture similarities and differences in the level of medical services advancement, multidimensional scaling method was applied. Results of the study allow stating that a significant advancement in the development of medical and social care services can be observed. However, Poland still lags behind other countries where development of these services remains on a high level.
Keywords: A11; C38; 330; services; health protection; social care